TAKALINTAR Learning Media: Supporting Elementary School Students' Counting Skills in Multiplication Materia - Abidah Ardelia; Setiyani; Ayu Try Lestari; Siti Valentina Pertiwi (Journal of Research and Educational Research Evaluation, 2024)
Numeracy skills in mathematics subjects, especially multiplication material, are categorized as low in third grade elementary school students. This study aims to determine the effectiveness of using TAKALINTAR learning media in improving counting skills in math subjects, especially multiplication in grade III elementary school students. This research is a quantitative approach. The research was conducted by all third grade students at SDN Kartini II, totaling 34 students. Techniques by collecting data in the form of tests, documentation and interviews. The results showed that the average pretest score before treatment was 46.47 lower than the average posttest score after treatment of 87.65. The pretest and posttest N-gain test results obtained were 0.7812 which was included in the high category. The results of the Wilcoxon Test hypothesis obtained the value of Asymp Sig. (2-tailed) = 0.000, which means that there is a significant increase in value. Therefore, it can be concluded that using TAKALINTAR learning media is effective to improve students' ability to count math, especially in multiplication learning material in class III SDN Kartini II Cirebon City.